The Effect of Doses of Cow Manure and NPK Fertilizer on the Growth and Yield of Purple Eggplant (Solanum Melongena L) Cultivars Mustang F1 - Hernawan, Deni; Jaenudin , Amran; Eviyati, Raden (Jurnal Agrosci, 2023)
The aim of this study was to determine the effect of doses of cow manure and NPK fertilizer on the growth and yield of purple eggplant plants (Solanum melongena L) Mustang cultivar F1, as well as to determine the relationship between the components of growth with components of purple eggplant plants (Solanum melongena L). The study was conducted in the village of Cigintung, Kuningan District, Kuningan Regency from September 07, 2019 to November 24, 2019. The location was at an altitude of 400 m above sea level (asl) with clay type, rainfall type C (Slightly wet). The method used was an experimental method with a factorial Randomized block Design (RBD), the treatment consisted of two factors that were repated three times. The first factor is cow manure consisting of three levels (K 1 = 10 tons/ha, K 2 = 15 tons/ha, K3 = 20 tons/ha). The second factor is NPK fertilizer consisting of three levels (N 1 = 100 kg/ha, N 2 = 200 kg/ha, N 3 = 300 kg/ha). The results showed that the different treatment dosages of doses of cow nanure and NPK fertilizer do not have a real effect on all ages observations on plant height, number of fruit plants, fruit length, fruit diameter, fruit weight per plant, fruit weight per plot.